Системи радіоелектронної розвідки і радіопротидії - Костров, Є. О. (ХНУРЕ, 2024)
This work explores the field of Radio Electronic Intelligence (REI) and Radio Countermeasures (RCM), examining their applications and advancements. REI systems play a crucial role in modern warfare, gathering vital information on enemy communications and electronic systems. RCM, on the other hand, focuses on disrupting and deceiving those same systems to achieve battle field superiority. We'll delve into the historical development of these technologies, tracking their evolution from rudimentary techniques to the sophisticated systems in use today.
Keywords: радіопротидія; радіоелектронна розвідка